2022
DOI: 10.2215/cjn.01610222
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Uremic Solutes from Dialysate by Activated Carbon

Abstract: Background and objectivesAdsorption of uremic solutes to activated carbon provides a potential means to limit dialysate volumes required for new dialysis systems. The ability of activated carbon to take up uremic solutes has, however, not been adequately assessed.Design, setting, participants, & measurementsGraded volumes of waste dialysate collected from clinical hemodialysis treatments were passed through activated carbon blocks. Metabolomic analysis assessed the adsorption by activated carbon of a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…Subsequent experimental studies showed that the effect of increasing the dialysate flow can be replicated by adding a powdered sorbent to the dialysate stream or introducing a sorbent into the dialysate stream between two dialyzers. 9,22,23 This study explored a potentially superior means to increase the bound solute clearances by use of a sorbent. A sorbent introduced into a recirculating system can provide high effective dialysate flows without increasing water use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent experimental studies showed that the effect of increasing the dialysate flow can be replicated by adding a powdered sorbent to the dialysate stream or introducing a sorbent into the dialysate stream between two dialyzers. 9,22,23 This study explored a potentially superior means to increase the bound solute clearances by use of a sorbent. A sorbent introduced into a recirculating system can provide high effective dialysate flows without increasing water use.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent experimental studies showed that the effect of increasing the dialysate flow can be replicated by adding a powdered sorbent to the dialysate stream or introducing a sorbent into the dialysate stream between two dialyzers. 9,22,23…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms to recycle or regenerate a smaller pool of dialysate are of increasing interest, and sorbent technology utilizing activated carbon is a prominent area of focus. Lee et al (5) now show us the effect that such technology can have on the metabolome as well.…”
mentioning
confidence: 94%
“…In this issue of CJASN , Lee et al . (5) expand our knowledge of the armamentarium to reduce various uremic solutes, particularly protein-bound ones, by focusing on dialysate. When solute concentrations in dialysate reach plasma-free concentrations (typically low for protein-bound substances), further removal of that solute down its concentration gradient is hindered.…”
mentioning
confidence: 99%
See 1 more Smart Citation